2022
DOI: 10.1109/toh.2021.3139890
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter Lateral Displacement Enables Friction Sensing and Awareness of Surface Slipperiness

Abstract: Human tactile perception and motor control rely on the frictional estimates that stem from the deformation of the skin and slip events. However, it is not clear how exactly these mechanical events relate to the perception of friction. This study aims to quantify how minor lateral displacement and speed enables subjects to feel frictional differences. In a 2alternative forced-choice protocol, an ultrasonic friction-reduction device was brought in contact perpendicular to the skin surface of an immobilized index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Even changing the approach angle of the robotic manipulator from perpendicular to 20° and 30° from normal (producing 8.9° and 19° force angles and 0.47 ±0.07 mm lateral movement after the first contact was detected) didn’t improve performance. In the follow up study using the same experimental setup in which a robotic manipulator brought a surface to an immobilised finger it was found that a submillimeter range lateral movement as small as 0.5 mm and, in some subjects, just 0.2 mm of the surface relative to the affixed rigid nail-phalangeal bone complex was sufficient to enable the subjects to differentiate surfaces based on their slipperiness (Afzal et al, 2022). Such small tangential movement deviations from a straight path when making contact with a surface are expected to occur during natural movement when humans reach and touch object surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even changing the approach angle of the robotic manipulator from perpendicular to 20° and 30° from normal (producing 8.9° and 19° force angles and 0.47 ±0.07 mm lateral movement after the first contact was detected) didn’t improve performance. In the follow up study using the same experimental setup in which a robotic manipulator brought a surface to an immobilised finger it was found that a submillimeter range lateral movement as small as 0.5 mm and, in some subjects, just 0.2 mm of the surface relative to the affixed rigid nail-phalangeal bone complex was sufficient to enable the subjects to differentiate surfaces based on their slipperiness (Afzal et al, 2022). Such small tangential movement deviations from a straight path when making contact with a surface are expected to occur during natural movement when humans reach and touch object surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explore the sensory processes underlying such friction perception when no intentional exploratory sliding movements are present. Previously, we have demonstrated that humans cannot perceive frictional differences when surfaces are brought in contact with an immobilized finger (Khamis et al, 2021b) unless there is a submillimeter lateral displacement (Afzal et al, 2022), or subjects made the movement themselves (Willemet et al, 2021). In the current study, subjects actively interacted with a device that can modulate friction using ultrasound, without an exploratory sliding movement, as they would when gripping an object to lift it.…”
mentioning
confidence: 99%
“…11(a), which demonstrates the MER tangential force and MER normal force during the whole grasping process, and also shows the minimum MER normal force calculated based on the MER tangential force, and the target MER normal force obtained based on the control strategy. Since the control strategy is to make the contact factor equal to 0.1, based on (10), the target MER normal force should be 11% more than the minimum MER normal force. From Fig.…”
Section: B Verification Of Grasping Force Control Strategymentioning
confidence: 99%
“…In addition, waiting until the macro slip has already occurred before starting the grasping force regulation makes it difficult to ensure that a large enough grasping force can be applied to stop the object before it falls. Actually, human hands can sense the friction conditions on the object surface and control the grasping force before macro slip occurs [9], [10]. In summary, grasping force control based on macro slip alone is deficient in terms of fineness and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, waiting until the macro slip has already occurred before starting the grasping force regulation makes it difficult to ensure that a large enough grasping force can be applied to stop the object before it falls. Actually, human hands can sense the friction conditions on the object surface and control the grasping force before macro slip occurs [9], [10]. In summary, grasping force control based on macro slip alone is deficient in terms of fineness and robustness.…”
Section: Introductionmentioning
confidence: 99%